Chinese Investment in Transport Infrastructure in the EU: a Stimulus for Development of Bilateral Trade? - K. A. Gemueva (Ассоциация независимых экспертов «Центр изучения кризисного общества» (in English: Association for independent experts “Center for Crisis Society Studies”), 2019)
Under the Belt and Road Initiative, particular importance is attached to transport networks development projects, including the creation of optimal transport routes and reorientation of existing supply chains based on the interests of China. This implies the active participation of Chinese companies in investing, financing and implementing projects in the field of transport infrastructure. The article examines the impact of Chinese investment in EU transport infrastructure facilities on the volume of freight traffic between China and the EU through these facilities. Most of the real Chinese investment are directed to the development of port facilities. European airports are also of great interest to Chinese investors, however, under the influence of many factors, only a few projects are successful. China is making significant efforts to establish direct rail links with EU countries. Nevertheless, the share of this type of transport is not yet comparable with freight turnover by sea and air, and future development is limited by a number of factors. Currently, COSCO’s investment in the Greek port of Piraeus is the only example of a significant increase in cargo turnover between China and the EU through an infrastructure under control, however, some ongoing projects could potentially repeat the success of COSCO in the near future. The author concludes that the approaches of the Chinese leadership to the transport infrastructure development are varied. Failures in the implementation of separate projects and the cautious attitude of Brussels towards Chinese investments do not stop China’s planned efforts focused on the long term perspective.